1998
DOI: 10.1111/j.1749-6632.1998.tb08197.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathological Factors of Human Breast Disease That Can Influence Optical Diagnosisa

Abstract: The 'normal' human female breast is a very complex organ that changes considerably during development, pregnancy and menopause. In addition, it is an excretory organ that, during lactation, discharges various metabolites and certain drugs that can be optically active. Optical diagnosis of breast cancers requires detection of differential concentrations of 1) various absorbers and scatterers or 2) native or exogenous fluorophores to distinguish cancers from surrounding 'normal' and benign breast tissues. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
1
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 58 publications
6
74
1
4
Order By: Relevance
“…The late decrease in THC and water correlates well with previous histologic studies showing both atrophy in well-vascularized lobular tissue and an increase in the fat-to-collagen ratio after menopause (15). This decrease is consistent with compositional analysis data showing lower blood and water content for fat versus glandular tissue (27).…”
Section: Quantities Versus Agesupporting
confidence: 89%
See 1 more Smart Citation
“…The late decrease in THC and water correlates well with previous histologic studies showing both atrophy in well-vascularized lobular tissue and an increase in the fat-to-collagen ratio after menopause (15). This decrease is consistent with compositional analysis data showing lower blood and water content for fat versus glandular tissue (27).…”
Section: Quantities Versus Agesupporting
confidence: 89%
“…Many investigators have used them to explore brain, breast, and muscle tissue, exploiting their enhanced penetrance relative to that of visible or ultraviolet radiation (1). In breast tissue, the principal NIR absorbers are assumed to be reduced hemoglobin (Hb-R), oxygenated hemoglobin (Hb-O 2 ), water (H 2 O), and lipids (15). NIR tissue spectroscopy offers a safe way to quantify these components and to view unique functional information with low-cost "point-of-care" devices.…”
mentioning
confidence: 99%
“…Certain collagens, especially type 1 collagen, is a major constituent of the dermis and fibrous stroma of breast. 42 It was shown that in normal breast tissues the fluorescence contribution of the collagen component decreased with increasing adipose tissue content, while it increased with increasing fibro-connective and glandular tissue content (as seen in Table 2). This agrees with the fact that collagen resides primarily in the dense fibrous stroma of the breast.…”
Section: Discussionmentioning
confidence: 90%
“…This agrees with the fact that collagen resides primarily in the dense fibrous stroma of the breast. 42 Taroni et al 43 measured absorption of collagen in healthy breast tissues using time-resolved transmittance spectroscopy, and showed that less fatty tissues are characterized by higher collagen concentration. Results of our study also showed that the collagen component has statistically higher contribution to the fluorescence of malignant and fibrous/benign breast tissues, as compared with that of normal adipose tissues (p<1×10 −6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation